Towards robust glucose chemical exchange saturation transfer imaging in humans at 3 T: Arterial input function measurements and the effects of infusion time. (29th September 2021) - Seidemo, Anina; Lehmann, Patrick M.; Rydhög, Anna; Wirestam, Ronnie; Helms, Gunther; Zhang, Yi; Yadav, Nirbhay N.; Sundgren, Pia C.; van Zijl, Peter C. M.; Knutsson, Linda
Abstract : Dynamic glucose‐enhanced (DGE) magnetic resonance imaging (MRI) has shown potential for tumor imaging using D‐glucose as a biodegradable contrast agent. The DGE signal change is small at 3 T (around 1%) and accurate detection is hampered by motion. The intravenous D‐glucose injection is associated with transient side effects that can indirectly generate subject movements. In this study, the aim was to study DGE arterial input functions (AIFs) in healthy volunteers at 3 T for different scanning protocols, as a step towards making the glucose chemical exchange saturation transfer (glucoCEST) protocol more robust. Two different infusion durations (1.5 and 4.0 min) and saturation frequency offsets (1.2 and 2.0 ppm) were used. The effect of subject motion on the DGE signal was studied by using motion estimates retrieved from standard retrospective motion correction to create pseudo‐DGE maps, where the apparent DGE signal changes were entirely caused by motion. Furthermore, the DGE AIFs were compared with venous blood glucose levels. A significant difference ( p  = 0.03) between arterial baseline and postinfusion DGE signal was found after D‐glucose infusion. The results indicate that the measured DGE AIF signal change depends on both motion and blood glucose concentration change, emphasizing the need for sufficient motion correction in glucoCEST imaging. Finally, we conclude that a longer infusion duration (e.g. 3–4 min) should preferably be used in glucoCEST experiments, because it can minimize the glucose infusion side effects without negatively affecting the DGE signal change. Abstract : Dynamic glucose‐enhanced (DGE) MRI was applied to healthy volunteers at 3 T using different glucoCEST protocols, including two different D‐glucose infusion durations and saturation frequency offsets. DGE arterial input functions were compared with venous blood glucose levels and a significant difference between arterial baseline and postinfusion DGE signal was found. The effect of subject motion on the DGE signal was investigated and the results indicate that DGE imaging at 3 T is challenging but feasible.